'Adhesion and release' nanoparticle-mediated efficient inhibition of platelet activation disrupts endothelial barriers for enhanced drug delivery in tumors. (February 2021) - Cao, Jinxu; Yang, Peng; Wang, Pengzhen; Xu, Shuting; Cheng, Yunlong; Qian, Kang; Xu, Minjun; Sheng, Dongyu; Li, Yixian; Wei, Yan; Zhang, Qizhi
Abstract: Activated platelets can maintain tumor vessel integrity, thereby leading to limited tumor perfusion and suboptimal antitumor efficacy of nanoparticle-based drugs. Herein, to disrupt the tumor vascular endothelial barriers by inhibiting the transformation of resting platelets to activated platelets, a TM33 peptide-modified gelatin/oleic acid nanoparticle loaded with tanshinone IIA (TNA) was constructed (TM33-GON/TNA). TM33-GON/TNA could adhere to activated platelets by specifically binding their superficial P-selectin and release TNA into the extracellular space under matrix metalloproteinase-2 (MMP-2) stimulation, leading to local high TNA exposure. Thus, platelet activation, adhesion, and aggregation, which occur in the local environment around the activated platelets, were efficiently inhibited, leading to leaky tumor endothelial junctions. Accordingly, TM33-GON/TNA treatment resulted in a 3.2-, 4.0-, and 11.2-fold increase in tumor permeation of Evans blue (macromolecule marker), small-sized Nab-PTX ( 10 nm), and large-sized DOX-Lip ( 100 nm), respectively, without elevating drug delivery to normal tissues. Ultimately, TM33-GON/TNA plus Nab-PTX exhibited superior antitumor efficacy with minimal side effects in a murine pancreatic cancer model. In addition, the TM33-GON/TNA-induced disrupted endothelial junctions were reversibly restored after the treatment because the number of platelets was not reduced, which implies a low risk of the undesirable systemic bleeding. Hence, TM33-GON/TNA represents a clinically translational adjuvant therapy to magnify the antitumor efficacy of existing nanomedicines in pancreatic cancer and other tumors with tight endothelial lining.